The Korean emissions trading scheme: business perspectives on the early years of operations. (3rd July 2018) - Suk, Sunhee; Lee, SangYeop; Jeong, Yu Shim
ABSTRACT: Korea's domestic emissions trading scheme commenced in January 2015. It targeted mainly industrial and power sectors, and compelled companies to transform how they manage energy efficiency and mitigate GHGs. This study sets out to explore how Korean companies evaluated their allocation position and engaged in emissions trading in the first compliance period, and to identify their views on trading barriers and policy expectations at the start of emissions trading. Questionnaire surveys and on-site interviews targeting Korean companies under the Korean emissions trading scheme were conducted at the start of operations (February to March 2015) and after the first compliance year (May 2016), respectively. Actual operation results are observed and compared with the survey findings. This study extrapolates implications for policy and presents suggestions for the government and the target companies in terms of how to improve the current emissions trading scheme in order to further stimulate emissions trading. POLICY RELEVANCE This study attempts to bridge the gap between companies and government policy in operating the domestic emission trading scheme in Korea. Empirical results, based on analysis of company-level data, reveal how businesses perceive K-ETS and how this relates to the operating results, which saw only limited trading of surplus emissions taking place in the early phase. Key barriers to active trading identified in the study include supply–demand imbalance, policy uncertainty and lack of preparedness of companies over carbon pricing. These barriers could be addressed by improved transparency of allowance allocation methods, possibly restricting carry-over of surplus allowances, ending policy uncertainty and providing more information to companies that can support companies' policy understanding of the carbon pricing based on the market mechanism. Targeted companies should proactively participate in emissions trading in the early phase, in order to learn from it and prepare for the future introduction of auctioning.